Retrospective analysis of quality of life after trans-sacral epiduroscopic laser neural decompression for chronic back pain - Karakulak, İskender and Yalçın, Çiğdem and Salman, Mehmet Alper and Çelebi, Nalan and Şahin, Altan (Acta Medica, 2026)
Objective: Low back pain is a common health problem that most adults experience at least once in their lifetime and significantly impacts healthcare costs, workforce productivity, and overall quality of life. Trans-Sacral Epiduroscopic Laser Neural Decompression (ELND) is a minimally invasive technique often used for patients with lumbar disc herniation. ELND offers advantages such as shorter operation times, faster recovery, and continuous communication with the patient during the procedure which reduces the risk of accidental nerve damage. We aimed to analyze the effects of ELND on pain and quality of life. Materials and Methods: A cohort of 89 patients diagnosed with lumbar disc herniation underwent the ELND procedure. The Medical Outcomes Study 36-item Short-Form Health Survey (SF-36) was used to evaluate the quality of life of 89 patients before and six months after the ELND procedure. Results: The analysis established a statistically significant increase in general health perception, physical functioning, physical role limitation, social functioning, vitality, pain, and general mental health subscales of the SF-36 questionnaire. However, the score for role limitation due to emotional problems decreased post-procedure. The median scores for general health perception increased from 54.3 to 68.3, physical functioning from 45.0 to 65.0, and pain from 10.6 to 63.0, among other subscales. The greatest improvement was observed in the physical role difficulty subscale. Conclusion: As a result, the ELND procedure is an effective treatment for patients with chronic low back pain, as demonstrated by significant reductions in pain scores and improvements in patient-reported quality of life. Specifically, the study found statistically significant enhancements in general health perception, physical functioning, physical role limitation, social functioning, vitality, and general mental health six months after the procedure. These findings indicate that ELND not only alleviates pain but also contributes to better physical mobility, daily functioning, and overall well-being.